2021
DOI: 10.1038/s41550-021-01483-0
|View full text |Cite
|
Sign up to set email alerts
|

The population of M dwarfs observed at low radio frequencies

Abstract: INTRODUCTORY PARAGRAPHCoherent low-frequency ( 200 MHz) radio emission from stars encodes the conditions of the outer corona, mass-ejection events, and space weather 1,2,3,4,5 . Previous low-frequency searches for radio emitting stellar systems have lacked the sensitivity to detect the general population, instead largely focusing on targeted studies of anomalously active stars 2,6,7,8,9 . Here we present 19 detections of coherent radio emission associated with known M dwarfs from a blind flux-limited low-frequ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 80 publications
0
62
1
1
Order By: Relevance
“…left or right handed) circular polarisation fraction. This is greater than the expected instrumental polarisation leakage (Callingham et al 2021) and also higher than many radio galaxies and blazars (e.g. Macquart & Fender 2004).…”
Section: Selection Of Pulsar Candidatesmentioning
confidence: 68%
See 1 more Smart Citation
“…left or right handed) circular polarisation fraction. This is greater than the expected instrumental polarisation leakage (Callingham et al 2021) and also higher than many radio galaxies and blazars (e.g. Macquart & Fender 2004).…”
Section: Selection Of Pulsar Candidatesmentioning
confidence: 68%
“…However, other sources of polarised emission exist, including rare flare stars, star-planet interactions, ultracool dwarfs, radio galaxies, and blazars (e.g. O'Sullivan et al 2013;Vedantham et al 2020;Pritchard et al 2021;Callingham et al 2021). These linear and circularly polarised sources will be further discussed in O' Sullivan et al, in prep.…”
Section: Non-detection Of Other Polarised Sources As Pulsarsmentioning
confidence: 99%
“…In that case, the emission is directly correlated with the strength of the planetary magnetic field. Coherent radio emission that could be associated with SPMI have been recently reported by Vedantham et al (2020); Turner et al (2021); Callingham et al (2021). If the radio signal shows a modulation with the orbital period of a known planet, or with the rotation period of the star, it could be furthermore possible to disambiguate the source of the detected radio emission (stellar or planetary magnetosphere, see e.g.…”
Section: Introductionmentioning
confidence: 83%
“…Cross-matching the archival information about that source on the sky would be helpful for early identification. By this means Pritchard et al (2021) identified 33 radio stars in the Rapid ASKAP Continuum Survey (RACS) and Callingham et al (2021) reported radio detection of 19 M dwarfs in LoTSS with ≈ 20% of the Northern sky processed. The catalog of brown dwarfs is far from complete in solar neighborhood so far, yet it will be greatly improved in future infrared surveys, e.g.…”
Section: Confirmation Of Flaring Ucd Candidatesmentioning
confidence: 95%